2022
DOI: 10.26499/surbet.v17i1.271
|View full text |Cite
|
Sign up to set email alerts
|

Prinsip Kerja Sama pada Tindak Tutur dalam Persidangan di Pengadilan

Abstract: Cooperative Principle on Speech Acts in The TrialsThe objective of this study is to examine the cooperative principle contained in the trials at Banda Aceh District Court. The cooperative principle examined in this study consists of the maxim of quality, the maxim of quantity, the maxim of manner, and the maxim of relevance. Data for the study was drawn from nine court cases involving specific and general crimes. Data collection was carried out by recording the trials with a voice recorder. Triangulation of da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Like conversations (1) and ( 2), where the officer only answered whether or not the questions asked by students were permissible, this shows that the indicator for compliance with the maxim of quantity is that it should not be excessive. Another indicator is also shown by (Nuthihar et al, 2022) that in complying with the maxim of quantity, the answers in the conversation must be very informative according to what is needed. This means that the target conversation answer must be precise and correct; at most, it is allowed to be what is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Like conversations (1) and ( 2), where the officer only answered whether or not the questions asked by students were permissible, this shows that the indicator for compliance with the maxim of quantity is that it should not be excessive. Another indicator is also shown by (Nuthihar et al, 2022) that in complying with the maxim of quantity, the answers in the conversation must be very informative according to what is needed. This means that the target conversation answer must be precise and correct; at most, it is allowed to be what is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, Nuthihar et al (2022) examined the application of the maxims of quality, quantity, manner, relevance, and cooperation in hearings at the District Court of Banda Aceh. This study found unfulfilled indicators required in the principle of cooperation.…”
mentioning
confidence: 99%